Studies on the human testis in vitro - Simpson, Barbara Jane Beaton (The University of Edinburgh, 1988)
The obligatory role of pituitary luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in the control of testicular function is well established. However there is increasing experimental evidence, largely in the rat, that quantitatively normal spermatogenesis not only requires an adequate local supply of testosterone but also the complex interactions between the various cellular components within the seminiferous tubules and interstitial compartments of the testis. The critical role of paracrine mechanisms in the testis may be reflected by the defective spermatogenesis in idiopathic male infertility where systemic levels of LH, FSH and testosterone are normal or elevated. Thus to further our understanding of the hormonal control of spermatogenesis and to define possible aetiological mechanisms in the infertile man, the study of paracrine mechanisms in the human testis is of paramount importance.

The approach to study paracrine mechanisms in the human testis was to establish in vitro techniques whereby individual components of the testis were isolated and specific functional markers defined so that their subsequent interaction could be further studied in vitro. At the same time, the delineation of these 'local' parameters were related to the overall functional states of the testis as defined by circulating levels of LH, FSH, testosterone and the histological assessment of spermatogenesis.

Testes were obtained at orchidectomy for prostatic carcinoma. Methods were established to examine the effect of intratesticular levels of testosterone and systemic levels of LH, FSH and testosterone on quantitative measures of spermatogenesis. For this purpose a simple iii technique which involved enumeration of spermatid nuclei in fixed testicular homogenates to determine daily sperm production was adopted. Daily sperm production in this group of ageing testes was generally lower than has been observed previously for younger men. Although intratesticular levels of testosterone varied widely there was no indication of an intratesticular deficiency of testosterone as a critical factor in subnormal spermatogenesis in the ageing testis.

Inhibin, a peptide marker of Sertoli cell function was measured in human testicular extracts by bio- and radioimmunoassay. The relationship observed between FSH and both inhibin bioactivity and immunoactivity imply that the role of inhibin in the testis may be somewhat different to the classical concept of FSH feedback.

A technique for the routine isolation of human Leydig cells was established. Human Leydig cells purified by Percoll density centrifugation were highly responsive to hCG, although sensitivity and receptor number were significantly lower compared to the rat. This system was used to test for the effects of putative paracrine factors on human Leydig cell function.

In conclusion, a number of in vitro techniques have been established and validated which provide a basis for future investigation of seminiferous tubule and Leydig cell function in the human testis.